An exploration of experiences and needs of novice critical care nurses to embark in the critical care areas - Rusila Ruslan (Kulliyyah of Nursing, International Islamic University Malaysia, 2021)
AN EXPLORATION OF EXPERIENCES AND NEEDS OF NOVICE CRITICAL CARE NURSES TO EMBARK IN THE CRITICAL CARE AREAS